Fetkin-hydro, a new thermo-hydrological algorithm for low-temperature thermochronological modeling - Sánchez Nassif, Francisco Gabriel Antonio (2021)
Despite two decades of major advances in the field of thermochronological modeling, state-of-the-art numerical implementations still rely mostly on burial and exhumation processes to explain radiometric measurements. Even though such an approach has proved valuable, failing to account for other first-order geological variables has led to misinterpretations and therefore, calls for a refinement. In this study a new version of the Fetkin (finite element temperature kinematics, Ecopetrol) program is presented. Its new algorithm couples time-dependent hydrological and thermal calculations, thus rendering thermochronological ages that, instead of being solely dependent on the kinematical evolution of a system, conditioning by the fluid flow is also present. In contrast with previous thermochronological models, this work considers the influence of effective stress on rock properties (porosity and permeability) and therefore, in thermal conductivity. Sensitivity analyses addressing relevant geological questions show not only the versatility of the code but also, new perspectives on forward low-temperature thermochronological modeling. Groundwater circulation through pure-sandstone settings produce colder thermal architectures than those obtained in impermeable domains. Differences in cooling ages from models with and without fluid circulation are up to 5 Myr. A 4-fold variation in thrusting rates (0.5 km/Myr to 2 km/Myr) produces a 15-Myr difference in cooling ages in models with fluid flow, which contrasts to much lower differences, only 2 Myr, in domains without (or minimal) fluid circulation. 2D thermal solutions in fold-bend-fold thrust belts composed of sandstones remain static despite substantial relief development by kinematic folding. A case-study from Western Argentina, in the Andean Precordillera, confirms the plausibility of the numerical algorithm here posed and raises new questions on the first-order thermal controls in settings under deformation.